2021
DOI: 10.3389/fpsyg.2021.751930
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Personality, Perfectionism, and Self-Efficacy as Predictors for Coping Strategies Based on Personal Resources

Abstract: Many psychological constructs as personality, perfectionism, and self-efficacy have been identified to have a strong contribution to teachers’ coping strategies, but how these variables collectively predict different types of coping has received little attention. The present study aimed to explore the personal resources (personality traits, perfectionistic strivings, and self-efficacy) which predict teachers’ proactive coping strategies. The sample study consisted of 284 pre-service teachers, with ages ranging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 94 publications
0
16
0
Order By: Relevance
“…In other words, over half of nursing students featured maladaptive perfectionism. The maladaptive perfectionism may have a negative impact on the functioning of students, their activities and the results related to the educational process [ 23 , 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In other words, over half of nursing students featured maladaptive perfectionism. The maladaptive perfectionism may have a negative impact on the functioning of students, their activities and the results related to the educational process [ 23 , 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, it is noted that there is a positive relationship between self-esteem and adaptive perfectionism [ 27 ]. Another important common element is their influence on social skills, e.g., coping with stress and interpersonal communication [ 28 ]. Consequently, self-efficacy and perfection are in a close relationship with social skills.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of the second mediation link (i.e., motivation profiles-workplace wellbeing-retention intention), findings indicated that kindergarten teachers in the “low value-high cost” profile (“high value-low cost” profile) had lower (higher) workplace wellbeing than those in the “moderate all” profile, which is consistent with person-organization fit theory. This meant that when employees’ motivations are highly aligned with those of their job, they are more likely to respond positively to organizational practices, resulting in increased positive affect and attitudes at work, indicating job wellbeing ( Fu et al, 2020 ; Samfira and Paloş, 2021 ). Additionally, the results also confirmed that individuals who perceive higher (lower) workplace wellbeing are more (less) motivated to stay with their current post, which consistent with model of wellbeing improvement and employer outcomes ( Sears et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is currently understood as a complex multidimensional and interactive trait ( Stoeber and Otto, 2006 ; Gaudreau and Thompson, 2010 ), characterized by a striving for perfection, extremely high standards for oneself, and stringent self-evaluations ( Stoeber, 2018 ). Perfectionism has been studied specifically in the educational context with regard to both teachers ( Stoeber and Rennert, 2008 ; Gluschkoff et al, 2017 ; Samfira and Paloş, 2021 ) and students ( Stoeber et al, 2009 ; Milyavskaya et al, 2014 ; Madigan, 2019 ). Yet, perfectionism also has many negative consequences ( Hill and Curran, 2015 ; Limburg et al, 2017 ; Sirois and Molnar, 2017 ; Smith et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%